New guidelines for children returning to sports after Covid-19 - McBride, D. L. (Journal of Pediatric Nursing, 2021)
Approximately 45 million children participate in some form of athletics. The COVID-19 pandemic has affected many aspects of their lives, including sports activities. Families are asking care givers questions about how best to ensure the safety of their children when returning to sports activities. The American Academy of Pediatrics has issued revised guidelines for children returning to athletic activities after COVID-19. These include strengthening the recommendations for cloth mask wearing for all children engaging in vigorous sports and clarifications of cardiac risks to children who have had COVID-19.